Pelatihan Penggunaan Google Formulir Berbasis Chatting Room di Masa Pandemi Covid-19 - Adila Salsabila; Ainun Salsabila; Annisa Syifa Rachmawati; Putri Rhamadyna; Rini Damayanti; Hani Nurlatifah; Anwar Mulyana; Hafiziani Eka Putri; Nadia Tiara Antik Sari (Jurnal Pengabdian Masyarakat PGSD, 2021)
This training is carried out as a service to elementary school teachers in providing technology-based student learning evaluations. The purpose of this service is to provide new knowledge related to the methods of providing learning evaluation and to improve the ability of elementary school teachers in using Google Forms chat room-based as a media for learning evaluation. The method used in this service was the steps implementation activities that include: (a) Interviewed teachers in UPTD SDN 9 Nagrikaler and observed the implementation of online learning; (b) Formulated the problem; (c) Coordinated with teachers, school principals, and field supervisors in determining programs; (d) Made a training media in the form of PowerPoints and videos; (e) Implemented the program. The results obtained based on the initial questionnaire data, the teachers' knowledge about the use of Google Forms was still minimum so that the training on the use of Google Forms chat room-based could help teachers to increase their knowledge in operating Google Forms in the 4.0 Industrial era. However, from the results of the interview, it was found that some teachers were difficult to operate Google Forms because they were constrained by its language and terms. In addition, teachers felt that Google Forms was effective enough to be used as a learning media and learning evaluation.